Morphology and biology of the bedbug, Cimex hemipterus (Hemiptera: Cimicidae) in the laboratory - Khan, Humuayun Reza; Rahman, Md Monsur (Dhaka University Journal of Biological Sciences, 2012)
Adult bedbugs collected from Fazlul Huq Muslim Hall, University of Dhaka were identified as Cimex hemipterus Fabricius (Hemiptera: Cimicidae). The bedbug species was reared and its morphology and biology were studied in the laboratory at room temperature 28 ± 4ºC and 70 ± 10% RH. The average incubation period of the eggs was 7.67 ± 2.08 days. Average nymphal duration was 53.67 ± 2.52 days. The five stadia (stage durations) of the five nymphs were 8.33 ± 0.58, 12.0 ± 1.0, 11.33 ± 0.58, 12.0 ± 1.0 and 10.0 ± 1.0 days, respectively. Average time required from egg laying to adult emergence was 61.67 ± 3.21 days. DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11510 Dhaka Univ. J. Biol. Sci. 21(2): 125-130, 2012 (July)